2018
DOI: 10.1021/acssuschemeng.7b03836
|View full text |Cite
|
Sign up to set email alerts
|

Thin and Small N-Doped Carbon Boxes Obtained from Microporous Organic Networks and Their Excellent Energy Storage Performance at High Current Densities in Coin Cell Supercapacitors

Abstract: This work reports the thinnest and smallest hollow N-doped carbon boxes among recently reported hollow N-doped carbon materials. Hollow and N-rich microporous organic networks (H-NMONs) were prepared by the azide–alkyne Huisgen cycloaddition of tetra­(4-ethynyl­phenyl)­methane and 1,4-diazido­benzene on the surface of Cu2O nanocubes and the successive acid etching of inner Cu2O. The Cu2O nanocubes played roles of templates and networking catalysts. The networking reaction generated N-rich triazole rings in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…[51][52][53] ME-MOPs can be utilized as platforms for the synthesis of new functional materials. [54][55][56][57][58] For example, through the incorporation of various precursors into ME-MOPs, new inorganic and composite materials could be synthesized. Moreover, ME-MOPs can extend the application elds of MOPs.…”
Section: Benefits Of Me-mopsmentioning
confidence: 99%
See 2 more Smart Citations
“…[51][52][53] ME-MOPs can be utilized as platforms for the synthesis of new functional materials. [54][55][56][57][58] For example, through the incorporation of various precursors into ME-MOPs, new inorganic and composite materials could be synthesized. Moreover, ME-MOPs can extend the application elds of MOPs.…”
Section: Benefits Of Me-mopsmentioning
confidence: 99%
“…17). 26, [54][55][56][57][58] First, the heat-treatment of the azide-alkyne click-based hollow MOP cubes under argon resulted in N-doped carbon nanocubes, showing excellent energy storage performance as electrode materials for supercapacitors (Fig. 17a and f).…”
Section: Synthesis Of New Materials Utilizing Me-mopsmentioning
confidence: 99%
See 1 more Smart Citation
“…The large surface area, good solvent and thermal stabilities, and tunable structures make MONs promising in diverse fields [3][4][5][6][7][8][9][10][11][12][13][14][15]. The Seung Uk Son's group reported the usage of MONs and their composites in catalysis [3][4][5][6], sensing [6], lithium ion batteries [8][9][10][11], and adsorption [12][13][14], underlining the broad application of MONs. Recently, Jia et al reported the metal-organic framework@MONs composite coated fiber for solid-phase microextraction of polycyclic aromatic hydrocarbons from environmental samples [15], revealed the potential of MONs in analytical chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Microporous organic networks (MONs) are a recent class of porous materials synthesized via the Sonogashira coupling reactions between rigid organic building blocks . The large surface area, good solvent and thermal stabilities, and tunable structures make MONs promising in diverse fields . The Seung Uk Son's group reported the usage of MONs and their composites in catalysis , sensing , lithium ion batteries , and adsorption , underlining the broad application of MONs.…”
Section: Introductionmentioning
confidence: 99%